STUDENTS’ NEED OF ENGLISH SKILLS IN HOTEL MANAGEMENT STUDY PROGRAM - Audi Yundayani; mariam brenda aprilialamongi (STIBA IEC JAKARTA, 2017)
The objective of the research is to find out students’ needs of English skills in Hotel Management Study Program. As a part of English as Specific Purposes (ESP), English comprehension should play an important role in Hotel Management study Program. This is a descriptive research that used observation, questionaire and interview. The data analysis and interpretation indicates that, 1)speaking skill is the major need of the hotel front officer, because oral communication is the most frequently used skill to communicate with the customers; 2) listening skill is required by students since speaking and listening are interrelated skills. It is important for the teacher to provide the suitable learning material and learning technique based on the requirement